Perceived organisational support and organisational citizenship behaviour: Key insights from institutions of higher learning in Kabale District, Uganda - Abaho, Felix; Agaba, Moses; Mwazuna, Alice Ngele (African Journal of Empirical Research, 2025)
This study evaluated the relationship between perceived organisational support and organisational citizenship behaviour among higher education institutions in Kabale District. The study was guided by Social Exchange Theory and followed a descriptive cross-sectional survey design targeting a total of 269 staff members, which included top management, administration, and academic and non-academic staff of the three selected institutions of higher learning in Kabale District. Using purposive and simple random sampling techniques, quantitative data was collected from 235 respondents using a structured questionnaire. Data was then analysed quantitatively using descriptive analysis, which entailed frequency and percentages, and tables were used to present the data. At the bivariate level, a Pearson correlation matrix was used to ascertain the relationships between organisational support and organisational citizenship behaviour. The findings revealed that all the constructs of perceived organisational support – fair treatment, career development and rewards and recognition – had a strong and positive correlation to organisational citizenship behaviour among institutions of higher learning in Kabale District, as indicated by (r = .662, p < 0.01), (r = .656, p < 0.01) and (r =.729, p < 0.01), respectively. The study concluded that perceived organisational support had a significant impact on organizational citizenship behaviour. The study recommends that institutions should regularly engage staff through open-door policies, mentorship programmes and feedback mechanisms to promote a culture of support and recognition. Design and implement structured recognition programmes for staff who demonstrate high levels of commitment, innovation, teamwork and voluntary contributions beyond their job roles. Offer staff continuous capacity-building workshops, scholarships for further studies and regular participation in academic conferences and training and Ensure transparency in promotions, task allocation and conflict resolution processes. Promote equity and inclusion across all academic and administrative departments.